ChemInform Abstract: Fenestranes in Synthesis: Unique and Highly Inspiring Scaffolds. Issue 9 (4th March 2014) - Boudhar, Aicha; Charpenay, Melanie; Blond, Gaelle; Suffert, Jean
Abstract Review: [125 refs.]